Emotion dysregulation in youths with obsessive-compulsive disorder and its implication for treatment - An exploratory study from the TECTO trial: A protocol and statistical analysis plan - Christine Lykke Thoustrup; Camilla Uhre; Valdemar Uhre; Melanie Ritter; Signe Vangkilde; Janus Engstrøm; Jane Lindschou; Christian Gluud; Anne Katrine Pagsberg; Markus Harboe Olsen (Contemporary Clinical Trials Communications)
Background: Research on improving psychotherapy for youths with obsessive-compulsive disorder (OCD), including cognitive behavioral therapy (CBT), should explore what works for whom and how by examining baseline moderators and potential mechanisms of change. Emotion dysregulation is proposed as an intermediate therapy factor in a transdiagnostic framework. This study investigates emotion dysregulation as an outcome, mechanism, and moderator of psychotherapy in youths aged 8–17 years with OCD. Methods: Data are from a randomized clinical trial and a parallel prospective study of healthy controls. Participants with OCD (n = 130; 121 in this study) were randomized to 14 sessions of either family-based CBT with exposure and response prevention versus family-based psychoeducation and relaxation training. We will; 1) assess if emotion dysregulation, measured by the Difficulties in Emotion Regulation Scale (DERS), decreases from baseline to end-of-treatment; 2) compare the proportion of participants with normative emotion regulation to a 90% reference interval from healthy controls (n = 90); 3) use linear regression to examine if baseline emotion dysregulation moderates treatment effects measured by the Children's Yale-Brown Obsessive-Compulsive Scale; 4) investigate if changes in emotion dysregulation mediate treatment effects; and 5) investigate the stability of emotion regulation over time in the healthy controls. Analyses 1–4 will be conducted for all OCD participants and separately for the two treatment groups. Two independent investigators will perform the analyses. Conclusion: This protocol and statistical analysis plan are presented to enhance analytical transparency and limit bias.